An Analysis of Billy Joel’s Song Lyric Vienna Using Psychoanalytic Literary Criticism Theory - Vanesa Liu; Putu Lirishati Soethama; Ida Ayu Made Puspani; Ni Ketut Alit Ida Setianingsih (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2023)
Psychoanalytic criticism employs Freud's and following theorists'